Operations management from Islamic perspective: an overview - Islam, Rafikul; E Azam, Md Siddique (Routledge, Taylor & Francis Group, 2024)
Successful businesses rely heavily on efficient and effective operations, making Operations Management a crucial function. Islamic perspectives on Operations Management have become increasingly popular in recent years. This is in part because of the ever-growing interest among Muslim consumers in halal options. Incorporating Islamic ethics and tenets into every facet of a company's operations is the goal of Islamic Operations Management (IOM). The use of halal-compliant materials and processes, fair treatment of staff and customers, waste reduction, and other green practices are all part of this perspective. IOM can facilitate organizations' adherence to regulations based on Islamic laws. Simultaneously, applying principles of IOM enhances the quality of products and services, thereby boosting customer satisfaction and business performance. Productivity improvement and cost-savings are added advantages in IOM. Moreover, it can help grow the company's image and bring in more customers. However, limited studies are available that shed lights on Operations Management through the lenses of Islam. Hence, this chapter aims to provide a comprehensive overview of Operations Management from an Islamic perspective. Several areas of Operations Management that have been reviewed are productivity improvement, halal supply chain, waste minimization, operations strategy, consultative decision-making, capacity planning, layout design, work design, quality management, and resource optimization. To achieve the objective, the chapter adopts the methodology of comprehensive review of existing literature in Operations Management and Islamic studies. This chapter is significant for Muslim business owners and executives concerned with conforming to halal standards and shari'ah principles.